Proteome profile analysis reveals regulatory mechanisms in the liver of Carassius auratus under short‐term salinity stress (10‰, 48 h) - Rui Zhao; Muhan Meng; Xiaolian Liu; Shuang Hao; Xin Luo; Ning Wu; Lin Ma; Sun Hongqing; Hongzheng You (Journal of Fish Biology, 2026)
Carassius auratus , a commercially important species in the ornamental aquarium industry, is sensitive to salinity fluctuations. In this study, 30 C. auratus of length 13.1 ± 2.9 cm and weight 103.8 ± 40.8 g/fish were placed into six plastic tanks (80 L) with five fish per tank. About 15 fish were exposed to 10‰ salinity for 48 h, while another 15 fish were kept in freshwater and continuously aerated (0‰) as a control. To investigate the effects of short‐term salinity stress (10‰, 48 h), proteomic profiling of the liver was conducted. Short‐term salinity stress resulted in 104 upregulated and 95 downregulated proteins in the liver of C. auratus . Gene ontology enrichment analysis indicated significant enrichment in areas such as proteolysis, nitrogen compound transport, cellular component, peptidase activity, acting on L‐amino acid peptides, endopeptidase activity, serine‐type peptidase activity and enzyme inhibitor activity. Furthermore, the Kyoto Encyclopedia of Genes and Genomes enrichment analysis identified mitogen‐activated protein kinase kinase kinase 7 (MAP3K7) as an essential regulated protein in the IL‐17 signalling pathway and glutamine synthetase (GS) in the arginine biosynthesis pathway. These findings suggest that short‐term salinity stress induces significant proteomic changes in C. auratus , with functional enrichment in peptide metabolism and enzyme regulation. Notably, MAP3K7 and GS may play crucial roles in coping with short‐term salinity stress, providing new insights into the proteomic regulatory mechanisms of C. auratus under short‐term salinity stress.